Anti-inflammatory activity of theophylline on carrageenan-induced paw edema in male wistar rats - ., K Srinivasa; Chandrasekhar, BVS; Srinivasa, J (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Evaluate the anti-inflammatory property of theophylline on rat hind paw edema using carrageenan-induced acute inflammatory model. Methods: Wistar male rats (150-200 gm) were divided into 7 groups- 3 standard groups, 3 test groups and 1 control group. Each group consists of six rats. A control group was treated with 0.2ml of normal saline, 3 standard groups were treated with different doses of Diclofenac (Standard drug): 5 mg/kg, 10 mg/kg, 15 mg/kg body weight, respectively and 3 test groups were treated with different doses of Theophylline (Test drug): 5 mg/kg , 10 mg/kg and 15 mg/kg, respectively. The anti-inflammatory property was assessed by plethysmograph. Results: Theophylline demonstrated a significant anti-inflammatory property at different dose levels when compared to controls (p > 0.05). However this anti-inflammatory activity was less as compared to standard drug. Conclusions: Theophylline exhibited a dose dependent anti-inflammatory activity in a carrageenan model of inflammation.